PENGARUH KEPEMILIKAN INSTITUSIONAL DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN DENGAN FREE CASH FLOW SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2011-2015 - Hairun Nisa; Edyanus Herman Halim; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of Institutional Ownership and Leverage (DER) of the Dividend Policy (DPR) by the Free Cash Flow as a moderating variable. The population in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2011-2015. The dependent variable in this study is the dividend policy (DPR), while the independent variable is institutional ownership and leverage (DER). This study has a population of 137 companies in the manufacturing companies listed in Indonesia Stock Exchange 2011-2015 period. This study using purposive sampling techniques and sample that meets as many as 44 companies. Data processing method using multiple regression analysis and regression moderation. 21:00 SPSS software version. The results showed that the variables Institutional Ownership, Leverage, and Free Cash Flow simultaneously significant effect on Dividend Policy. While partially, variable Institutional Ownership significant negative effect on Dividend Policy, Leverage has no effect and no significant effect on Dividend Policy, Free Cash Flow to moderate the relationship Institutional Ownership Dividend Policy and Free Cash Flow are not moderate the relationship Leverage the Dividend Policy.Keywords: Dividend Policy (DPR), Institutional Ownership, Leverage (DER), and Free Cash Flow.